2021
DOI: 10.1002/cctc.202100063
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium Nanoparticle Size Effects on the CO2 Reforming of Methane and Propane

Abstract: The CO2 (dry) reforming of hydrocarbons offers an opportunity to convert greenhouse gases into synthesis gas, which can further transform to various valued products. Here we explore the influence of Rh particle size and support on the reforming of propane and methane. To that end, Rh nanoparticles with controlled sizes varying from 1.6‐8.0 nm were synthesized following a polyol reduction method and then dispersed on three different solids: CeZrO2, ZrO2, and CeO2. Catalytic turnover rates along with advanced ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…However, little information was found in the literature on the effect of Pt nanoparticle sizes on the reaction rate of DRM reactions. In a similar material system, however, Gascon et al 60 investigated the effect of rhodium (Rh) particle size on DRM reaction rates, where Rh nanoparticles were deposited on three substrates, namely CeO 2 , CeO 2 –ZrO 2 , and ZrO 2 . It was found that the DRM reaction rates on the catalysts showed a linear correlation with the Rh nanoparticle size in the range of 1.6–8.0 nm.…”
Section: Resultsmentioning
confidence: 99%
“…However, little information was found in the literature on the effect of Pt nanoparticle sizes on the reaction rate of DRM reactions. In a similar material system, however, Gascon et al 60 investigated the effect of rhodium (Rh) particle size on DRM reaction rates, where Rh nanoparticles were deposited on three substrates, namely CeO 2 , CeO 2 –ZrO 2 , and ZrO 2 . It was found that the DRM reaction rates on the catalysts showed a linear correlation with the Rh nanoparticle size in the range of 1.6–8.0 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The growth in global sustainable energy demands more blue hydrogen for zero-emission vehicles and chemical plants. Also, efforts to decarbonize the fossil fuel-based petrochemical industry have surged for more CO 2 capture and utilization. Dry reforming would be an attractive route to increase syngas production (CO and H 2 ). Dry reforming of propane remains a challenging reaction, as it delivers low yields of syngas products with moderate conversion of both CO 2 and C2–C3 compared to the higher performance of methane dry reforming. , Figure presents the thermodynamics of C1–C3 dry reforming in the form of Gibbs free energy versus temperature, showing that dry reforming of C2–C3 requires lower reaction temperatures than dry reforming of methane. , Specifically, propane appears more favorable at notably lower temperatures, while dry reforming of ethane and methane noticeably requires higher temperatures. Ultimately, the utilization of CO 2 for C2–C3 dry reforming produces more moles of CO and hydrogen, as described in eqs –. normald ry reforming of methane : nobreak0em0.1em⁡ CH 4 nobreak0em0.1em⁡ + nobreak0em0.1em⁡ CO 2 nobreak0em0.1em⁡ nobreak0em0.1em⁡ 2 CO nobreak0em0.1em⁡ + nobreak0em0.1em⁡ 2 H 2 ( Δ H 298 ° 249 kJ mol 1 ) normald ry reforming of ethane : nobreak0em0.1em⁡ nobreak0em0.1em⁡ normalC 2 normalH 6 + 2 CO 2 4 CO + <...…”
Section: Introductionmentioning
confidence: 99%
“…Dry reforming would be an attractive route to increase syngas production (CO and H 2 ). Dry reforming of propane remains a challenging reaction, as it delivers low yields of syngas products with moderate conversion of both CO 2 and C2–C3 compared to the higher performance of methane dry reforming. , Figure presents the thermodynamics of C1–C3 dry reforming in the form of Gibbs free energy versus temperature, showing that dry reforming of C2–C3 requires lower reaction temperatures than dry reforming of methane. , Specifically, propane appears more favorable at notably lower temperatures, while dry reforming of ethane and methane noticeably requires higher temperatures. Ultimately, the utilization of CO 2 for C2–C3 dry reforming produces more moles of CO and hydrogen, as described in eqs –. Several propane dry reforming studies utilized reactive catalysts based on Ni, Ru, Re, and Rh, supported by Al 2 O 3 , ZrO 2 , TiO 2 , SiO 2 , CeO 2 , , and MgO . Solymosi et al studied the catalytic dry reforming of propane at 650 °C over various catalysts, highlighting that these catalysts with Al 2 O 3 and TiO 2 supports loaded with Rh showed the low to moderate conversion of propane and CO 2 in the range of ∼40 to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Dry reforming of propane may also run in parallel leading to syngas production (CO/H 2 ) (10) [10,11]. (10) Carbon dioxide may also be involved in the reverse Boudouard reaction (11), removing coke from the catalyst surface and, thus, improving catalyst stability [5]. CO 2 + C ↔ 2CO ∆H 0 298K = 172.4 kJ/mol (11) The major benefit of the ODP process is the utilization of CO 2 , of which emissions into the atmosphere have increased rapidly during recent decades and nowadays is considered as one of the main greenhouse gases resulting in global warming and, therefore, major climate change [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…(10) Carbon dioxide may also be involved in the reverse Boudouard reaction (11), removing coke from the catalyst surface and, thus, improving catalyst stability [5]. CO 2 + C ↔ 2CO ∆H 0 298K = 172.4 kJ/mol (11) The major benefit of the ODP process is the utilization of CO 2 , of which emissions into the atmosphere have increased rapidly during recent decades and nowadays is considered as one of the main greenhouse gases resulting in global warming and, therefore, major climate change [4,12]. However, CO 2 is a thermodynamically stable compound (∆G f = −394 kJ•mol −1 ), the reduction of which requires high energy reactants combined with active and selective catalysts as well as optimal reaction conditions to gain a thermodynamic driving force.…”
Section: Introductionmentioning
confidence: 99%